2021
DOI: 10.3233/jae-201564
|View full text |Cite
|
Sign up to set email alerts
|

Influence of voltage fluctuations on core vibration of a UHV shunt reactor

Abstract: A new core vibration calculation method of UHV shunt reactors is proposed to deal with the problem that vibration parameters of the core of an ultra-high voltage (UHV) shunt reactor cannot be measured on site. A series of tests have validated that the method can calculate the vibration parameters of a UHV shunt reactor core with different voltage ratios. The method is adopted to study the influence of nodal voltage fluctuations of the UHV AC tie line on the core vibration characteristics of a UHV shunt reactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In [17], it proposes a new triangular core structure for reactors, which achieves vibration damping by means of dispersing the electromagnetic forces on the core. In [18], it investigated the effect of the number of iron core air gaps on the vibration of a UHV shunt reactor, and its research shows that within the range of the reasonable number of air gaps, the fewer the number of iron core air gaps, the weaker the vibration intensity of the reactor. In [19][20], it takes the double-column UHV shunt reactor as the research object.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [17], it proposes a new triangular core structure for reactors, which achieves vibration damping by means of dispersing the electromagnetic forces on the core. In [18], it investigated the effect of the number of iron core air gaps on the vibration of a UHV shunt reactor, and its research shows that within the range of the reasonable number of air gaps, the fewer the number of iron core air gaps, the weaker the vibration intensity of the reactor. In [19][20], it takes the double-column UHV shunt reactor as the research object.…”
Section: Introductionmentioning
confidence: 99%
“…In [18], it investigated the effect of the number of iron core air gaps on the vibration of a UHV shunt reactor, and its research shows that within the range of the reasonable number of air gaps, the fewer the number of iron core air gaps, the weaker the vibration intensity of the reactor. In [19][20], it takes the double-column UHV shunt reactor as the research object. It proposes the method of adjusting the reactor core air gap length to achieve the goal of vibration reduction of the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-high voltage (UHV) shunt reactors play key roles in the power grid; ensuring its safe and stable operation can greatly improve the reliability of UHV power grid operation. Due to the existence of external excitation or internal electromagnetic force, electrical equipment during the actual operation is often run in mechanical motion and other states [2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…The primary focus of current studies is on simulating and conducting experiments to understand the vibration mechanism of reactors. Guo et al [1] introduced an innovative approach for calculating and analyzing core vibrations in ultra-high voltage shunt reactors. Their study revealed the relationship between voltage fluctuations and core vibration characteristics.…”
Section: Introductionmentioning
confidence: 99%